Randomized, Multicenter Trial of ARTSS-2 (Argatroban With Recombinant Tissue Plasminogen Activator for Acute Stroke). Issue 6 (June 2017) - Barreto, Andrew D.; Ford, Gary A.; Shen, Loren; Pedroza, Claudia; Tyson, Jon; Cai, Chunyan; Rahbar, Mohammad H.; Grotta, James C.; Ajani, Zahra; Alexandrov, Andrei V.; Cherches, Igor; Coull, Bruce; et al.
Abstract : Background and Purpose—: We conducted a randomized exploratory study to assess safety and the probability of a favorable outcome with adjunctive argatroban, a direct thrombin-inhibitor, administered to recombinant tissue-type plasminogen activator (r-tPA)–treated ischemic stroke patients. Methods—: Patients treated with standard-dose r-tPA, not receiving endovascular therapy, were randomized to receive no argatroban or argatroban (100 μg/kg bolus) followed by infusion of either 1 (low dose) or 3 μg/kg per minute (high dose) for 48 hours. Safety was incidence of symptomatic intracerebral hemorrhage. Probability of clinical benefit (modified Rankin Scale score 0–1 at 90 days) was estimated using a conservative Bayesian Poisson model (neutral prior probability centered at relative risk, 1.0 and 95% prior intervals, 0.33–3.0). Results—: Ninety patients were randomized: 29 to r-tPA alone, 30 to r-tPA+low-dose argatroban, and 31 to r-tPA+high-dose argatroban. Rates of symptomatic intracerebral hemorrhage were similar among control, low-dose, and high-dose arms: 3/29 (10%), 4/30 (13%), and 2/31 (7%), respectively. At 90 days, 6 (21%) r-tPA alone, 9 (30%) low-dose, and 10 (32%) high-dose patients were with modified Rankin Scale score 0 to 1. The relative risks (95% credible interval) for modified Rankin Scale score 0 to 1 with low, high, and either low or high dose argatroban were 1.17 (0.57–2.37), 1.27 (0.63–2.53), and 1.34 (0.68–2.76), respectively. The probability that adjunctive argatroban was superior to r-tPA alone was 67%, 74%, and 79% for low, high, and low or high dose, respectively. Conclusions—: In patients treated with r-tPA, adjunctive argatroban was not associated with increased risk of symptomatic intracerebral hemorrhage and provides evidence that a definitive effectiveness trial is indicated. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique Identifier: NCT01464788. Abstract : Supplemental Digital Content is available in the text.